PENGGUNAAN BENTUK RANCANGAN BUTIR TES UJIAN AKHIR SEMESTER DALAM MENGUKUR KOMPETENSI MAHASISWA PADA PERGURUAN TINGGI NEGERI DI MEULABOH ACEH BARAT - Rusma Setiyana; Cukri Rahmi Niani (universitas teuku umar, 2019)
This study aims to determine the form of tests used in measuring student competence and to analyze the level of Bloom's Taxonomy used by faculty. This research used a descriptive research model with a mixed method approach i.e. quantitative-qualitative research. The research data obtained were in the form of interview and documents including syllabus and test items of the final examination designed by the faculty in the university of Teuku Umar Meulaboh. The data were analyzed using a checklist technique and univariate percentage. The results showed that the forms of tests used are devided into 4 categories namely; (a) essay, (b) true-false and essay, (c) multiple choices and essay, and (d) multiple choices, true – false, and essay test. Furthermore, the most dominant use is the level of remember, then followed by the level of understand, apply, and analyze; 45%, 42%, 11% dan 2% respectively. Keywords: form of tests, Bloom’s Taxonomy, final test